Anxiété langagière, communication médiée par les technologies et élicitation des clitiques objets du français L2 - Adel Jebali (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
Technology mediated communication is seen by many authors as less anxiety-provoking and more conducive to a better language production from L2 learners than face-to-face. However, others believe that there is no difference between the two communication channels in regard to linguistic performance. We conducted an experiment with a group of intermediate-advanced learners of French as a second and foreign language. We measured their linguistic performance during the realization of two types of tasks: face to face and mediated by Skype. Participants also answered two questionnaires: one aimed to measure their degree of language anxiety and the other one to gauge their level of computer anxiety. The results of this study show that French L2 learners perform better in distance communication context and produce more object clitics, but this only occurs when the elicitation of these units is action-based.